A escola no acampamento do MST: institucionalização e gestão estatal da escola itinerante Carlos Marighella - Amboni, Vanderlei (2014)
The thesis contains a study on the School in MST Camp: Institutionalization and Management of State Itinerant School Carlos Marighella. The problem of this study lies in the way of managing the traveling school in the MST camp, the contradiction is present with regard to the class struggle and interests defending, as Brazil is, par excellence, the land of large estates and, he, a deep social inequality in rural and urban areas, that can be characterized as social apartheid. In this regard, it is noteworthy that the construction of the Itinerant School has history and school history in the MST has the story of the struggle for agrarian reform. In these struggles, the Paraná bears the mark of the explosion of class struggle in the countryside, whose centrality is in the mechanization of agriculture, land concentration and construction of dams in Santiago Jump and Itaipu, which displaced more than 3,000 families from their land. In the struggle for land, northwest region of Paraná brings the land occupation and school occupation as dispute space. There is, in this struggle, the occupation of Fazenda Santa Filomena, in Planaltina of Paraná, and with it the construction of Camp Elias Gonçalves de Meura. This camp was built Itinerant School Marighella Carlos, who was born as a public school in 2004, which started teaching activities in a stable. Therefore, our purpose was to this school, meet its internal structure and forms of management. So our object is the school management. So we ask ourselves: How is the management of a school of MST in the capitalist state structure? There is an autonomous management from the State? Management mechanisms that are present in the Itinerant School? Collegiate bodies that are present in the school structure? How is the social control of the Itinerant School? In this sense, the school management is the MST or no state control over school management? Given these issues, our intention was to investigate the School Itinerant Carlos Marighella both the organizational aspects, the management, the administrative, educational and financial dimensions, from 2004 to 2013. Therefore, we undertook a bibliographic nature of research and interviews. In literature, the empirical sources consulted were the texts and MST works on education, and the documents produced by the MEC, SEED and State Councils of Education relevant to Education Field and Itinerant Schools. Besides these, we also drew the texts produced by several researchers who analyzed the Itinerant Schools in the different aspects of studies. Interviews were conducted with members of the MST Education Sector, educators and students of EI, public officials and school community camping. The reflections on the school management, despite being a singularity as pedógica experience, to be tensioned by the conflict of land, EI is not the government school, nor he directed. She is the dual management, but brings in your organization elements of the socialist school of work as selforganization in the training process. This is the meaning of this research thesis answered.